EFL STUDENTS’ PERCEPTION TOWARD THE INTERACTION IN ONLINE LEARNING - Luh Putu Restu Adi Utami (Wacana Saraswati Majalah Ilmiah Tentang Bahasa Sastra Dan Pembelajarannya, 2021)
The spread of COVID-19 across the world influences different aspects of the world, one of which is education. There are many ways the government has done to keep it from expanding through social distance learning, one of which is through online distance learning. This study aimed to identify students’ perceptions of online learning experiences. The research was conducted at SMK CIS Bali with twenty tenth-grade students. Data were obtained using a questionnaire and interview to gather information on EFL students’ perceptions of interaction in online learning. Questionnaires are provided to students using the Google form after all content in one semester of online learning has been completed. The data collected from the questionnaire were quantitatively evaluated and qualitatively described. The findings revealed that students perceived a moderate level of interaction in online learning, but some reasonsaffected their interactions in online learning.